Solution-Processed Titanium Dioxide Ion-Gated Transistors and Their Application for pH Sensing - Subramanian, Arunprabaharan; Azimi, Mona; Leong, Cheng Yee; Lee, Siew Ling; Santato, Clara; Cicoira, Fabio (Frontiers in Electronics, 2022)
Titanium dioxide (TiO2) is an abundant metal oxide, widely used in food industry, cosmetics, medicine, water treatment and electronic devices. TiO2 is of interest for next-generation indium-free thin-film transistors and ion-gated transistors (IGTs), due to its tunable optoelectronic properties, ambient stability solution processability. In this work, we fabricated TiO2 films using a wet chemical approach and demonstrated their transistor behavior with room temperature ionic liquids and aqueous electrolytes. In addition, we demonstrated the pH sensing behavior of the TiO2 IGTs with a sensitivity of ~ 48 mV/pH. Furthermore, we demonstrated a low temperature (120 ˚C), solution processed TiO2-based IGTs on flexible PET (polyethylene terephthalate) substrates, which were stable under moderate tensile bending.